Strings attached - Blundell, Judy. (Scholastic Press, 2011)
When she drops out of school and struggles to start a career on Broadway in the fall of 1950, seventeen-year-old Kit Corrigan accepts help from an old family friend, a lawyer said to have ties with the mob, who then asks her to do some favors for him.